2022
DOI: 10.3389/fneur.2022.896651
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Intermittent Theta Burst Stimulation for Stroke Patients With Upper Limb Impairments: A Systematic Review and Meta-Analysis

Abstract: BackgroundUpper limb impairments are one of the most common health problems of stroke, affecting both motor function and independence in daily life. It has been demonstrated that intermittent theta burst stimulation (iTBS) increases brain excitability and improves upper limb function. Our study sought to determine the role of iTBS in stroke recovery.ObjectiveThe purpose of this study was to determine the efficacy of iTBS in individuals with upper limb impairments following stroke.MethodsThe databases used incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Besides, standard 600-pulse stimulation showed a better effect on motor function improvement compared to 1200 pulses. The results are consistent with previous studies [ 16 , 52 , 53 ]. Additionally, two studies [ 34 ] integrated different forms of rTMS and reported that bi-hemispheric stimulation (1 Hz rTMS to the UH M1 and iTBS to the AH M1) was associated with better motor performance when compared to unilateral modulation [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Besides, standard 600-pulse stimulation showed a better effect on motor function improvement compared to 1200 pulses. The results are consistent with previous studies [ 16 , 52 , 53 ]. Additionally, two studies [ 34 ] integrated different forms of rTMS and reported that bi-hemispheric stimulation (1 Hz rTMS to the UH M1 and iTBS to the AH M1) was associated with better motor performance when compared to unilateral modulation [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…According to the baseline neurophysiological characteristics of healthy participants before intervention, the Extra Trees model accurately classified responders to TBS. Interventions for post-stroke motor dysfunction in the upper and lower limbs using TBS are currently based on interhemispheric competition models ( Chieffo et al, 2016 ; Huang et al, 2022 ; Vink et al, 2023 ). In the future, these models may improve post-stroke paralysis by customizing iTBS and cTBS to an individual’s responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 presents the details of all the stimulation protocols. Traditional tDCS and Theta Burst Stimulation (TBS) protocols are widely used neuromodulation approaches for various neurological disorders ( Bologna et al, 2015 ; Bornheim et al, 2022 ; Huang W. et al, 2022 ; Zhang et al, 2022 ). For example, anodal tDCS increases neuronal excitability, producing long-term potentiation (LTP)-like effects, while cathodal tDCS induces long-term depression (LTD)-like effects ( Rroji et al, 2015 ; Kronberg et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%